노인층 옥외활동의 질적 GIS를 활용한 근린환경 특성의 해석 - 서울시 저소득 노인밀집지역 무수골을 대상으로 - 윤예화; Yun Ye-hwa; 성종상; Sung Jong-sang (한국조경학회지, 2022)
선행연구에 따르면 옥외활동은 노인의 신체적, 정신적, 사회적 건강에 긍정적 영향을 미치는 것으로 알려져 있다. 노화가 진행될수록 일상생활이 도보권 내 근린환경과 밀접해지는 가운데, 건강증진을 위한 ‘활동적 노화’와 ‘고령친화’는 근린환경에서 실제 이루어지는 옥외활동 수준과 그 인식에 좌우되는 것이다. 이에 본 연구에서는 도시 내저소득 노인밀집지구의 사례에서 노인의 옥외활동이 근린환경에서 어떻게 이루어지는지 알아보고자 하였다. 또한 옥외활동의 촉진ㆍ억제요인이 작용하는 맥락을 시간적ㆍ공간적 여건 및 개인적ㆍ사회적 여건에 따라 고찰하고자 하였다. 이를 위해 서로 다른 접근방식인 관찰조사와 인지지도 및 심층 인터뷰를 혼합함으로써 질적 GIS 정보를 다각적으로 해석해보았다. 먼저 행태관찰조사를 통해 옥외활동이 이루어지는 주요공간의 활동패턴과 이용자별, 시간대별 특성을 맵핑하여 분석하였다. 또한 거주 노인의 인지지도를 수집하고 주요 외부공간별 근린환경에 대한 인식과 활동목적 등을 인터뷰하여 옥외활동이 이루어지는 상호맥락을 고찰하였다. 연구결과 ‘시야가 개방’된 쾌적한 공간으로 향하는 ‘집 바로 앞 골목’의 접근성이나 인지성이 높을 경우 나가고자 하는 욕구가 보다 원활하게 실현되는 것으로 보인다. 노인층에게 ‘익숙함’이란 것이 매우 중요한 가운데, 공간에 대한 인지성과 접근성을 높임으로써 심리적 경계를 허물어 주는 것이 매우 중요할 것으로 보인다. 또한 사회적 교류와 갈등관계는 노인층의 공간 점유양식에 크게 영향을 미치는 요인으로 확인되었다. Prior studies have shown positive effects of outdoor activities on the elderly’s physical, mental and social health. ‘Active aging’ and ‘age-friendly’ neighborhood can be created by modifying the experiences and perceptions of the outdoor environment. This study aims to investigate the outdoor activities of the elderly living in a low-income elderly concentrated area and their perception of the neighborhood environment. We also explored the context of interactions between the facilitators and inhibitors of outdoor activities on the basis of temporal, spatial, and social conditions. We used a mixed method approach by collecting two different types of qualitative GIS data : observation maps of the main places and individual cognitive maps with in-depth interviews. The observational map analysis indicated that the preferred places and activity patterns differ by age, gender, and size of the group. The cognitive map and interviews demonstrated that the elderly’s activity goals and perception of the landscape differ by places such as forests, parks, streams, open-spaces, vegetable gardens, and alleys. The elderly’s desire for outdoor activities can be better fulfilled when their front doors and alleys are well-connected to an open-sight pleasant space. Familiarity is an important factor for the elderly, therefore it is important to remove the psychological and physical barriers by increasing the legibility and accessibility of places. In addition, social interactions and conflicts can have a significant influence on the elderly’s occupation of space in the neighborhood environment.